PENGARUH TATA LETAK GUDANG TERHADAP KELANCARAN PRODUKTIVITAS BONGKAR MUAT DI GUDANG PT. NCT - Tiffany Dwi Januarny; Cundo Harimurti (Jurnal Logistik Indonesia, 2021)
PT. NCT is a company engaged in domestic goods delivery service sector. As for the problem happened to PT. NCT is the placement of the finished items in the warehouse is still not in order and not match the place, this results the item confused with other item, and the hand pallet passageway and forklift became narrow, and complicated the storage items storage and taking process. The independent in this research was warehouse layout, meanwhile dependent variable was unloading productivity. This research used qualitative method. The population in this research was the warehouse employee of PT. NCT with samples of 30 respondents, with sampling technique used saturated sample technique. The data collecting technique used was questionnaire, each respondent was given 20 questions, then data processed with SPSS statistics analysis. Based on the result of this research, shows that there is significant and positive effect between variable of warehouse layout on variable of unloading productivity of 36,8%, meanwhile the other 63,8% explained by other variable out of the variable used in this research. Based on the result of calculation of simple linear regression test, obtained result of regression equation of Y = 5,917 + 0,874X. Meanwhile on the result of hypothesis test shows the value of t count > t table (4,035 > 2,048). This means H0 is rejected and H1 is accepted, or there are effects between Warehouse Layout on Unloading Productivity.